Mathematics Teachers' Self-Efficacy in Saudi Arabia Following Reform of Mathematics Curricula - Bakri awaji (Faculty of Education - Port Said University, 2023)
AbstractThe significance of teachers' self-efficacy (TSE) in school psychology research has increased due to its implications for teaching effectiveness, instructional practices and students' academic achievement. TSE has its roots in Rotter's theory of locus of control, which was later extended by Bandura (1977, 1986, 1997) to emphasise the role of personal competencies. TSE refers to teachers' confidence in their ability to teach their students, support their learning and help them achieve academic success. This study sought to determine the level of mathematics TSE in the Kingdom of Saudi Arabia after the reform of the mathematics curriculum and to investigate any differences in the levels of TSE that might be attributed to gender or teaching experience. The research adopted a quantitative approach, employing an online questionnaire to collect data from 360 male and female mathematics teachers. The questionnaire included 16 items derived from the previous literature and adapted to fit with the changes to the curriculum. The results indicate a high level of TSE among mathematics teachers, with no significant differences based on gender or experience.